Specialized Proresolving Mediators Facilitate the Immunomodulation of the Periodontal Ligament Stem Cells - Yu, Ning; Rakian, Audrey; Dean, Afsah; Van Dyke, Thomas E. (Frontiers in Dental Medicine, 2021)
Recent investigations into the regulation of inflammation in periodontitis have revealed that chronic inflammatory diseases like periodontitis are characterized by an imbalance in proinflammatory and pro-resolution mediators, and can be characterized by a failure of resolution pathways in the late stages of the acute inflammatory response. The pro-resolution mediators, termed Specialized Pro-resolving Mediators (SPM), comprise the Lipoxins, Resolvins, Protectins and Maresins that are derived from arachidonic acid or omega-3 polyunsaturated fatty acids. In animal studies, treatment of periodontitis with topical SPMs returns the inflammatory lesion to homeostasis with regeneration of all components of the periodontal organ lost to disease. In this report, we investigate the immunomodulatory role of SPMs in periodontal ligament stem cells (PDLSCs). Primary porcine PDLSCs (pPDLSCs) were stimulated with IL-1β and IL-17 in vitro to simulate periodontal inflammation in the presence or absence of SPMs. We found that IL-1β and IL-17 synergistically activated pro-inflammatory genes of pPDLSCs and altered the immune phenotype of pPDLSCs including key signaling pathways. Addition of SPMs rescued the pPDLSCs phenotype and induced further production of additional SPMs, which was reflected by upregulation of the requisite enzymes 12- and 15- Lipoxygenase by pPDLSCs. We then interrogated the immunomodulatory actions of pPDLSCs on monocyte/macrophages, focusing on porcine CD14/CD16/CD163 markers using flow cytometry. We utilized the CD14+CD16+/CD14+CD16- ratio and CD163 on monocytes/macrophages to differentiate between a pro-inflammation phenotype (lower ratio) and a resolution of inflammation phenotype (higher ratio). We found that conditioned medium from pPDLSCs treated with cytokines and Maresin 1 increased the CD14+CD16+/CD14+CD16- ratio and had the highest CD163 expression. We conclude that in an inflammatory environment, pPDLSCs become pro-inflammatory and exert immunomodulatory functions. Maresin 1 resolves the inflammation by acting on pPDLSCs directly and by shifting monocytes/macrophage phenotype to pro-resolution dominance.